Post‐release dispersal and breeding site suitability of reintroduced populations of the Crested Ibis in Shaanxi Province, China. Issue 5 (14th May 2021) - Wang, Fang; Li, Min; Zhang, Ya‐Shuai; Zhao, Wen‐Ai; Liu, Dan‐Ni; Zhang, Ya‐Zu; Zhang, Hu; Ye, Xin‐Ping; Yu, Xiao‐Ping
Abstract : Post‐release dispersal of reintroduced animals refers to the process of successful colonization and failed settlement. To ensure the establishment and persistence of a reintroduced population, the impacts of different factors on the post‐release dispersal of captive‐bred animals must be assessed. In this article, we focused on two reintroduced Crested Ibis ( Nipponia nippon ) populations in Shaanxi Province, China. We applied multiple approaches to evaluate the effects of age, body weight, sex, timing of release, size of acclimatization cages for rewilding, and duration of acclimatization on the survival rate of released populations. The results showed that the survival capacity of released individuals was negatively correlated with their age in Ningshan County (Spearman, r = −0.344, p = 0.03, n = 41). The released ibises in Ningshan and Qianyang County had an average dispersal direction of 210.53° ± 40.54° (Rayleigh's z test: z = 7.881 > z 0.05, p < 0.01, n = 13) and 27.05° ± 2.85° (Rayleigh's z test: z = 5.985 > z 0.05, p < 0.01, n = 6), respectively, suggesting that the dispersal tended to clump in one direction in both sites. The MaxEnt modeling results indicated that the most significant environmental factor responsible for breeding site selection in Ningshan County was paddy field. In Qianyang County, precipitation affects nest site selection through influencing food availability. In conclusion, the evaluation framework used in this study can serve as an example for developing conservation priorities on the landscape scale for more animal reintroductions.